Turn-Taking Mechanism and Power Relations in United States Presidential Debates between Donald Trump and Kamala Harris on September 11, 2024 - Padma Dewi Kalingga Putri; Hilmi Akmal (Journal of Pragmatics Research, 2025)
This research aims to examine the Turn-Taking Mechanism and Power Relations that emerged in the 2024 United States Presidential Debate between Donald Trump and Kamala Harris. This research uses a qualitative method with the theory of Turn-Taking Mechanism proposed by Jacob L Mey and Michel Foucault’s theory of power, which places power as something that is spread in a network of social relations and manifested through language. Turn-Taking Mechanism in political debates serves as an important mechanism to reveal the dynamic of power relations between candidates. Data were obtained from official transcripts and video recordings on the ABC News debate YouTube Channel, then analyzed to identify patterns of the Turn-Taking Mechanism, such as Taking the Floor, Holding the Floor, and Yielding the Floor. The analysis showed that the Turn-Taking Mechanism in this debate was not as orderly as it should be in cooperative communication. Through Foucault’s candidate perspective, power relations in this debate can be seen through the way candidates organize and distribute discourse in the public communication space. The research also found that moderator interventions, which aim to maintain the rules of Turn-Taking in the course of the debate, were often undermined by the candidates’ discursive power practices, thus showing that power in debates is fluid, resistive and constantly shifting depending on the dynamic of interaction. Moreover, this research is expected to contribute to the development of Linguistic studies, especially Pragmatics in the field of politics, as well as explore further the relation between discourse analysis and power relations.